Doing well by doing good? The case of Magrabi Foundation - Shalaby, Mohammad Saeed (AUC Knowledge Fountain, 2016)
This study aims at empirically investigating the business case of corporate social responsibility for private hospitals. The study attempts to explore the possible monetary and non-monetary business benefits for the Magrabi Hospital, in the Community Outreach Program carried out by the Magrabi Foundation. In addition, the study further attempts to understand the role of these potential benefits, on the deci- sion-making processes of the top executives in private hospitals. The study uses a mixed qualitative and quantitative approach through a three stages process for examining the qualitative and quantitative roles of CSR, as well as the evaluation of the strategic relevance of these evaluation components. The study findings suggest the existence of a business case, in the relationship of Magrabi Hospital and Magrabi Foundation. This business case was demonstrated by providing evidence to a positive effect on the Hospital from the involvement in the Foundation activities on both quantitative and qualitative levels. However the study showed that there is limited integration of the relationship as a strategic option in Ma- grabi Hospital plans. The study concludes by recommending a preliminary framework, for private hospitals that aim to engage in CSR initiatives and achieve a benefit the business, as well as future research on the subject.